Tìm x biết: (1+2y)/18=(1+4y)/24=(1+6y)/6x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{1}{32}\) = 2-5
\(\dfrac{1}{8}\) = 2-3
0,5 = \(\dfrac{1}{2}\) = 2-1
0,25 = \(\dfrac{1}{4}\) = 2-2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(-27\right)^5:32^3\)
\(=\left[\left(-3\right)^3\right]^5:\left(2^5\right)^3\)
\(=\left(-3\right)^{15}:2^{15}\)
\(=\left(-3:2\right)^{15}\)
\(=\left(-\dfrac{3}{2}\right)^{15}\)
\(\left(-27\right)^5\):\(32^3\)
=-14348907:32768
=-437,8938904
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1
1) -1/4 + 3/4 : 6
= -1/4 + 1/8
= -1/8
2) (-1/6 - 5/13 + 11/12) - (8/13 - 7/6 - 1/3)
= -1/6 - 5/13 + 11/12 - 8/13 + 7/6 + 1/3
= (-1/6 + 7/6) + (-5/13 - 8/13) + (11/12 + 1/3)
= 1 - 1 + 5/4
= 5/4
3) (-2/3)² . 3/5 + √(4/25) : 9/4 - 1,75
= 4/9 . 3/5 + 2/5 . 4/9 - 7/4
= 4/9 . (3/5 + 2/5) - 7/4
= 4/9 - 7/4
= -47/36
Bài 2
1) -1 2/5 - x = 2/3 - 4/5
-7/5 - x = -2/15
x = -7/5 + 2/15
x = -19/15
2) [√(9/64)+ x] - 1 1/2 = -3/4
3/8 + x - 3/2 = -3/4
x = -3/4 - 3/8 + 3/2
x = 3/8
3) 2.3ˣ⁺² + 4.3ˣ⁺¹ = 10.3⁶
3ˣ⁺¹.(2.3 + 4) = 10.3⁶
3ˣ⁺¹ . 10 = 3⁶ . 10
3ˣ⁺¹ = 3⁶
x + 1 = 6
x = 6 - 1
x = 5
![](https://rs.olm.vn/images/avt/0.png?1311)
(0,8)⁵ : (0,4)⁶
= (4/5)⁵ : (2/5)⁶
= 1024/3125 : 64/15625
= 16 . 5
= 80
\(\left(0,8\right)^5:\left(0,4\right)^6\\ =\left(\dfrac{4}{5}\right)^5:\left(\dfrac{2}{5}\right)^6\\ =\dfrac{1024}{3125}:\dfrac{64}{15625}\\ =16.5\\ =80\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\dfrac{11}{4}\right)^{12}:\left(-\dfrac{11}{4}\right)^{11}\)
\(=\left(-\dfrac{11}{4}\right)^{12}:\left(-\dfrac{11}{4}\right)^{11}\)
\(=\left(-\dfrac{11}{4}\right)^{12-11}\)
\(=\left(-\dfrac{11}{4}\right)^1\)
\(=-\dfrac{11}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\dfrac{3}{7}\right)^2.\left(-7\right)^4\\ =\left(\dfrac{3}{7}\right)^2.7^4\\ =\left(\dfrac{3}{7}\right)^2.7^2.7^2\\ =9.49\\ =441\)
(1+2y)/18=(1+6y)/6x=(1+2y+1+6y)/18+6x=(2+8y)/18+6x=(1+4y)/9+3x
=>(1+4y)/9+3x=(1+4y)/24 =>9+3x=24 =>3x=15 =>x=5
(1+2y)/18=(1+6y)/6x=(1+2y+1+6y)/18+6x=(2+8y)/18+6x=(1+4y)/9+3x
=>(1+4y)/9+3x=(1+4y)/24 =>9+3x=24 =>3x=15 =>x=5
Nhé bạn !